Integrating Humanitarian Demining with Remote Control Tech in Educational Process - Dziuba, Petro; Neroba, Vadym; Chukanov, Andrii; Shcherbliuk, Volodymyr; Shkvarskiy, Oleksandr (Journal of the University of Zulia, 2023)
The aim of the work is to investigate the possibility of introducing the system of humanitarian demining into the educational process of higher education institutions (HEIs) of Ukraine. The introduction of modern equipment against improvised explosive devices explosive items, for example remotely controlled ones, was also studied. Methods used: content analysis, semi-structured interviews, and self-assessment of the sapper’s competence. The conducted research for the first to describe the results of the possibility of introducing a system of humanitarian demining in HEIs of Ukraine, where it has not yet been introduced. It was found that educational institutions for military training in various fields have sufficient material and technical resources for professional training of demining personnel. It is also proposed to renew or renovate the demining equipment, as well as introduce a project activity on the development of remotely controlled mechanisms against explosive items into the educational process. The results can be useful to researchers and teachers who are working on updating the content of education in accordance with the current security needs. Further research should be conducted on the monitoring of new demining equipment.